Beta-alanine improves punch force and frequency in amateur boxers during a simulated contest - Donovan, T.; Ballam, T.; Morton, J. P.; Close, G. L. (International Journal of Sport Nutrition and Exercise Metabolism, 2012)
The aim of this study was to test the hypothesis that Beta-alanine supplementation improves punch power and frequency in amateur boxers during a simulated contest. Sixteen amateur boxers (each approximately 6 yr experience) were assigned to beta-alanine (n = 8; 1.5 g 4 times/d for 4 wk) or placebo supplementation (n = 8) after initially being assessed for baseline punch performance. Before and after the supplementation period, all boxers completed a simulated contest consisting of 3 × 3-min rounds (interspersed with 60-s rests) on a punching bag (with a force transducer attached). Each round involved performing 2 min 50 s standardized punching (standardized jab, cross combination) based on notation analysis, whereas the last 10 s involved maximal-output punching (standardized jab, cross combination), during which time punch force and frequency were recorded. Postcontest blood lactate was significantly increased in the Beta-alanine group (presupplementation 9.5 ± 0.9 mmol/L, postsupplementation 12.6 ± 0.5 mmol/L, p < .05), whereas the placebo group showed no change (presupplementation 8 ± 2.8 mmol/L, postsupplementation 7.0 ± 2.7 mmol/L; p > .05). During the 10-s maximal-output punching, changes in mean punch force (?-alanine 20 ± 1.01 kg, placebo 1 ± 1 kg) and punch frequency (Beta-alanine 5 ± 4, placebo -2 ± 3) were greater (p < .05) in the Beta-alanine-supplemented group. The authors conclude that beta-alanine supplementation improves punching performance in amateur boxers and suggest that this supplementation protocol may also prove ergogenic for other combat-related sports.